Anarchy and complexity (2016)
This paper draws a philosophical parallel between the characteristics of anarchism with the sciences of complexity. The absence—??, an—of a ruling principle—arche, ????—is the conditio sine qua non, it is claimed, for a further search for ground and fundament. The most basic features common to both anarchism and complexity are the absence or critique to control as well as the importance of self-organization. Embracing the theory of complexity inevitably leads towards the acceptance of anarchy. A spirit of anarchy pervades complexity science even if: a) it has not been explicitly thematized, or b) it has not been the explicit concern of researchers and scholars working in the field. © 2016, Emergent Publications. All rights reserved.